Factors that influence the dominance of an enterprise reference architecture: A comparative case study - Rogante, Elena; van Wessel, Robert; de Vries, Henk (Journal of Standardisation, 2022)
Reference architectures provide template solutions for particular domains and can therefore be considered as standards. This study investigates whether diversity in enterprise reference architectures is likely to continue or if one reference architecture will gain dominance in the market. More specifically, we examine factors that lead to market dominance. We use the literature on standards battles, the Technology Acceptance Model (TAM), and the Technology-Organization-Environment (TOE) framework to analyse factors for dominance. In this field, network effects apply and provide a force towards the dominance of a single architecture. However, factors contributing to multiple standards are more relevant, as well as those from TAM and TOE, since reference architectures differ slightly in their added value for various categories of stakeholders. Empirical data from 19 expert interviews provide further insights into the factors that influence the dominance of an enterprise reference architecture. Our results show that it is important that the content and value of reference architectures are straightforward and understandable, not only for architects but for all stakeholders. We extend current standards battles literature by applying it to a new area and combining it with TAM and TOE. We provide an innovative and extensive list of factors that influence the dominance of one standard and the continued coexistence of multiple standards and relate these to phases of technology development. This list can form a framework for future standards battle research. From the practical perspective, the annex may help parties involved in standard battles to position themselves in the technology development phase, better predict the outcome of the battle, and enhance the possibility to influence that outcome. More specifically, our paper will help adopters of enterprise reference architectures to make better-informed choices. Suppliers of reference architectures can use the findings to stimulate market adoption of their model.